Sistem Pakar Deteksi Penyakit Kambing Menggunakan Certainty Factor Berbasis Android - Rizki Setyawan, Muhammad (Universitas Sari Mutiara Indonesia Medan, 2023)
Diseases pose a serious threat to the health and well-being of livestock in the livestock industry, especially in goat farming. In addressing this challenge, the use of intelligent technologies such as expert systems is becoming increasingly important. Expert systems are computer programs that can mimic the knowledge and skills of human experts in specific fields. One of the methods used in expert systems is the Certainty Factor method. Certainty Factor is an inference method used in expert systems to measure the level of confidence in a conclusion based on predefined rules. This method takes into account certainty or uncertainty factors in decision-making. In the detection of diseases in goats, the Certainty Factor method considers the symptoms found in goats and calculates the confidence weights for each disease that may be the cause of those symptoms. This research aims to develop an Android-based expert system application using the Certainty Factor method. The results obtained from this research show that the application can assist goat farmers in identifying diseases that affect their livestock, enabling early intervention and reducing losses due to animal deaths.